Model of NFT Implementation on Web SSO over OpenID Connect and Oauth 2.0 protocols - Esa Fauzi; Sy Yuliani; Yenie Syukriyah; Azizah Zakiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Single Sign-On (SSO) is a mechanism that allows users to access various services using a single set of login credentials. However, in SSO implementations, there are still challenges related to security and authentication management, particularly attacks targeting the Identity Provider (IDP). To address this, the use of Non-Fungible Tokens (NFTs) as proof of IDP ownership has been proposed as a solution to enhance security in the authentication mechanism. The utilization of NFTs in SSO with OpenID Connect and OAuth 2.0 has the potential to improve security and convenience in the authentication process due to the unique and non-duplicable nature of NFTs. The results of this research present a model and design of SSO with NFTs on OpenID Connect and OAuth 2.0. An SSO application with login, register, and password recovery features was also developed to provide convenience to users during the login process. The findings conclude that the utilization of NFTs in SSO with OpenID Connect and OAuth 2.0 has the potential to enhance security and convenience in the authentication mechanism. Further research is needed to explore aspects such as scalability, in-depth security analysis, testing in real-world scenarios, improvement of integration and interoperability, as well as comparative analysis with other SSO technologies.